Publication of a Quality Content as a Tool for Strengthening Consumer Trust in the Modern Business World (A Social Science and Entrepreneurship Journal, 2025)
This article discusses how digital platforms and contentcreators play a crucial role in the success of growingbusinesses, particularly in the culinary sector. By leveragingsocial media, small businesses can strengthen their brandingand build consumer trust through high-quality, relevantcontent. A case study of a successful culinary entrepreneurdemonstrates that consistent and innovative brandingstrategies significantly contribute to business growth in acompetitive market. This research uses a qualitativeapproach, with data collection methods includingobservation and in-depth interviews. The findings emphasizethe importance of collaboration between entrepreneurs andcontent creators in building a strong brand, attractingcustomers, and fostering a loyal community. Furthermore,this article provides practical strategies that aspiringentrepreneurs, especially the younger generation, canimplement when starting digital-based businesses. Byleveraging digital technology and creative ideas,entrepreneurs can create new job opportunities andcontribute to local economic progress.
Keywords: Digital Platform; Branding; High-Quality Content; Modern Business; Customer Trust